2019
DOI: 10.1111/jvh.13156
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of telbivudine and tenofovir disoproxil fumarate in preventing hepatitis B vertical transmission: A real‐life practice

Abstract: Mother‐to‐child transmission (MTCT) is a major obstacle in the elimination of hepatitis B virus (HBV) infection. Telbivudine (LdT) and tenofovir disoproxil fumarate (TDF) are the two most common antiviral medicines for preventing MTCT. However, the efficacy and safety of LdT and TDF in preventing HBV vertical transmission during the second to third trimester have not been compared rigorously. Therefore, we carried out a prospective multicentre cohort study of chronic hepatitis B in mothers with HBV DNA > 106 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 47 publications
(55 reference statements)
3
50
0
Order By: Relevance
“…Additionally, only 1 child was HBsAg(+) by 1 year age, and an intention-to-treat analysis indicated an MTCT rate of 4.01% with LdT treatment. 27 Similar to our findings, subsequent studies demonstrated that LdT antiviral treatment could effectively reduce MTCT, whereas MTCT occurred in 2.8%-14.7% patients in the untreated control groups. 24 the differences in the efficacy of LdT administration during the first trimester (early pregnancy group) and the second or third trimesters of pregnancy (middle pregnancy group) in preventing MTCT.…”
Section: Telbivudine Administration In Gravidas With Chronic Hbv Insupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, only 1 child was HBsAg(+) by 1 year age, and an intention-to-treat analysis indicated an MTCT rate of 4.01% with LdT treatment. 27 Similar to our findings, subsequent studies demonstrated that LdT antiviral treatment could effectively reduce MTCT, whereas MTCT occurred in 2.8%-14.7% patients in the untreated control groups. 24 the differences in the efficacy of LdT administration during the first trimester (early pregnancy group) and the second or third trimesters of pregnancy (middle pregnancy group) in preventing MTCT.…”
Section: Telbivudine Administration In Gravidas With Chronic Hbv Insupporting
confidence: 91%
“…Our group enrolled 312 CHB gravidas who hadn't accepted LdT starting at 24 weeks of gestation; 51.0% (159/312) displayed undetectable HBV DNA at delivery. Additionally, only 1 child was HBsAg(+) by 1 year age, and an intention‐to‐treat analysis indicated an MTCT rate of 4.01% with LdT treatment . Similar to our findings, subsequent studies demonstrated that LdT antiviral treatment could effectively reduce MTCT, whereas MTCT occurred in 2.8%‐14.7% patients in the untreated control groups .…”
Section: Telbivudine Administration In Gravidas With Chronic Hbv Infesupporting
confidence: 87%
See 2 more Smart Citations
“…The risk of HBV MTCT is closely related to high HBV DNA levels, and the risk of immunoprophylaxis failure starts to increase when HBV DNA levels exceed 200 000 IU/mL. Data mainly from Asia have confirmed the efficacy and safety of peripartum antiviral therapy using tenofovir disoproxil (TDF) in addition to BDV and HBIG to control HBV MTCT in mothers with high risk of HBV MTCT . The 2016 study by Pan and colleagues from China provides strong evidence to support the efficacy of this strategy .…”
Section: Interventions To Prevent Mother‐to‐child Transmission Of Hbvmentioning
confidence: 99%